Pengaruh Price to Book Value, Economic Value Added, dan Market Value Added terhadap Return Saham pada Perusahaan Badan Usaha Milik Negara yang terdaftar di Bursa Efek Indonesia Tahun 2020-2022 - Kisma, Lara; Anggita, Wenni; Ridwan, Muhammad Qomaruddin (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This study aims to analyze the effect of Price to Book Value, Economic Value Added, and Market Value Added on Stock Returns in State-Owned Enterprises listed on the Indonesia Stock Exchange in 2020-2022. The number of samples used in this study was 19 companies with purposive sampling techniques. The type of data used is secondary data. This study uses a quantitative approach with data analysis methods and hypothesis testing using descriptive statistical analysis and panel data regression analysis. The results of the study show that partially Price to Book Value has a positive effect on Stock Returns, while Economic Value Added and Market Value Added have no effect on Stock Returns. Simultaneously, Price to Book Value, Economic Value Added, and Market Value Added have a positive effect on Stock Returns in State-Owned Enterprises listed on the Indonesia Stock Exchange in 2020-2022